Association between inflammatory cytokines and other Biochemical parameters in patients after 48 hrs of first myocardial infarction (MI) - Farhood, Hattf B. (University of Thi-Qar Journal of Science, 2022)
Myocardial infarction (MI) is a term used to describe a heart attack that occurs when blood flow to theheart muscle reduced, and plaque builds up in the lining of the coronary arteries, resulting in insufficient oxygen supply. Thestudy was conducted on a number of participants, including 100 cases and 70 controls, who were matched for gender andage. The blood indicators in question were examined using standard laboratory techniques and equipment. The studyaimed to study the relationship between inflammatory cytokines, lipid profiles, and transaminase enzyme in patients48 hours after myocardial infarction. The results indicated  that there are differences between cases and controls for inflammatory cytokines (IL-8, IL-12, and IFN-Αα). Moreover, total cholesterol (TC), low-density lipoprotein (LDL), and highdensity lipoprotein (HDL) were decreased in cases in comparison with controls, while triglyceride (TG) was high in patients after MI. However, patients' aspartate transaminase (AST) levels were meaningfully higher than in controls.